Source constraints using ground motion simulations. - Kiratzi, A. (Bulletin of the Geological Society of Greece, 2013)
We study the source characteristics of the 9 August 1912, Mw 7.4, Mürefte (Ganos) earthquake that ruptured the Ganos Fault in the westernmost segment of the North Anatolian Fault. We apply the stochastic method for finite-faults in order to simulate strong ground motion acceleration using different fault geometries in terms of the rupture initiation and the length of the fault. A first-order approximation of the site effect variation is achieved following an empirical approach based on the topography gradient as a proxy for site-effect. The simulated ground motions, which are calculated at phantom stations, over a grid covering the area of study, satisfactorily produce the regions which were more severely shaken during the 1912 event. We simulate ground motions using a conservative fault length of 50 km (one land segment) which is able to explain the location of the surface ruptures but is not able to reproduce the surface extent of strong shaking. We then use a longer fault of approximately 120 km, extending to Saros Bay in the west and to Marmara Sea in the east. The synthetic peak ground acceleration values, indicate a segmented nature of the fault, have at least two patches of strong shaking and significantly predict the observed macroseismic intensities of the 1912 earthquake. Further constrain in our modelling is posed by surface ruptures, with small releasing and restraining structures and 1.5–5.5 m right-lateral offsets, that have been previously measured by others, at 45 sites of the on-land 50-km-long fault section.